The Role of Teachers’ Interpersonal Behaviors in Learners’ Academic Achievements - Zhang, Qian (Frontiers in Psychology, 2022)
In the context of English as a foreign language classroom, affections that form between teacher and students may affect the teaching/learning process. This review aimed to investigate the related studies on the effect of teacher-learner interpersonal relationships on learners’ educational performance in English as a Foreign Language (EFL) educational contexts. This review concluded that there is a significant constructive correlation between teacher-learner interpersonal relationships and learners’ academic achievement. Learners are required to have some sense of belonging to improve their educational performance. Moreover, other positive emotional factors such as grit, well-being, self-efficacy, academic engagement, motivation, and foreign language enjoyment can mediate the association between teacher-learner interpersonal relationships and learners’ academic success. The study concludes with some implications for English learners, English language teachers, and English language teacher trainers. The ideas can improve their awareness of teacher-student interpersonal relationships, including teacher stroke, rapport, and teacher immediacy and their role in improving learners’ foreign language learning.